Individuation Crisis and Ego Gendering in Pre‐schoolers—Emphasizing the Female Hero in Girls' Development - Fabioola, Jetthe (Journal of analytical psychology, 2025)
This paper offers a new perspective on early individuation, e.g., seeing nightmares of pre‐schoolers as an expression of a first individuation crisis and part of the child's separation from the symbiosis with the containing mother/motherly. Focusing on girls, the author suggests that the female hero plays an underexposed yet vital role in girls' individuation. The female hero is the female counterpart to the male hero, which in a patriarchal culture has been commonly assumed to be the source of support at this stage. It enables girls—supported by father and imagination—to liberate themselves and meet the demands for adjustment to the fatherly world while gendering their ego as feminine with an openness to the other sex where opposites are at play. Based in classical and post‐Jungian theory, the author presents empirical material gathered during anthropological fieldwork in a Copenhagen primary school and includes dream, drawing and narrative to show how the female hero emerges and becomes an important element in resolving the developmental and individuation crisis girls may encounter as they enter into the educational system and venture further out into the world. A client case connects un‐resolve in preschool to a later mid‐life crisis. Cet article avance une nouvelle perspective sur l'individuation précoce, par exemple en considérant les cauchemars des enfants d'âge préscolaire en tant que l'expression d'une première crise d'individuation faisant partie du processus de séparation entre l'enfant et la symbiose avec la mère contenante/maternelle. En se concentrant sur un groupe de filles, l'auteur suggère que l'héroïne féminine joue un rôle sous‐exposé et pourtant vital dans l'individuation chez les filles. L'héroïne féminine est le pendant du héros masculin qui, dans une culture patriarcale, a été généralement considérée comme la source de soutien à ce stade. Elle permet aux filles—soutenues par une idée du père et par l'imagination – de se libérer et de répondre aux exigences d'adaptation au monde paternel tout en confirmant à leur ego sa dimension féminine avec une ouverture à l'autre sexe dans un contexte où les opposés sont en jeu. S'appuyant sur la théorie classique et post‐jungienne, l'auteur présente un d'matériel recueilli au cours d'un travail de terrain anthropologique dans une école primaire de Copenhague et utilise le rêve, le dessin et la narration pour démontrer comment l'héroïne féminine émerge et devient un élément important pour la résolution d'une crise de développement et d'individuation que les filles peuvent rencontrer à l'entrée dans le système éducatif ou quand elles s'aventurent dans le monde social. Le cas d'une patiente relie l'absence de résolution à l'âge préscolaire à une crise plus tardive à l'âge mûr. Dieser Aufsatz bietet eine neue Perspektive auf die frühe Individuation, indem er beispielsweise Albträume von Vorschulkindern als Ausdruck einer ersten Individuationskrise und als Teil der Trennung des Kindes von der Symbiose mit der containenden Mutter/dem Mütterlichen betrachtet. Der Autor konzentriert sich auf Mädchen und weist darauf hin, daß die Heldin eine unterbelichtete aber dennoch wichtige Rolle bei der Individuation von Mädchen spielt. Die Heldin ist das weibliche Gegenstück zum männlichen Helden, von dem in einer patriarchalischen Kultur allgemein angenommen wird, daß er in dieser Phase die Quelle der Unterstützung ist. Es ermöglicht Mädchen – unterstützt durch den Vater und ihre Vorstellungskraft – sich zu befreien und den Anforderungen der Anpassung an die väterliche Welt gerecht zu werden, während sie gleichzeitig ihr Ego als weiblich auszurichten und sich dem anderen Geschlecht gegenüber offen zu zeigen lernt, wo Gegensätze im Spiel sind. Basierend auf klassischer und postjungianischer Theorie präsentiert die Autorin empirisches Material, das während anthropologischer Feldforschung in einer Kopenhagener Grundschule gesammelt wurde. Anhand von Träumen, Zeichnungen und Erzählungen zeigt sie, wie die Heldin entsteht und zu einem wichtigen Element bei der Lösung der Entwicklungs‐ und Individuationskrise wird, die Mädchen erleben können, wenn sie in das Bildungssystem eintreten und sich weiter in die Welt hinauswagen. Ein Klientenfall verbindet Ungelöstes im Vorschulalter mit einer späteren Midlife‐Crisis. Questo articolo offre una prospettiva sull'individuazione precoce, ad esempio considerare gli incubi dei bambini in età prescolare come espressione di una prima crisi di individuazione e come parte della separazione dalla simbiosi con la madre/contenitore. Focalizzandosi sulle ragazze, l'Autrice suggerisce che l'eroina femminile giochi un ruolo vitale, sottovalutato, nell'individuazione delle ragazze. L'eroina femminile è la controparte femminile dell'eroe maschile, che, nella cultura patriarcale, è stato generalmente visto come la sorgente della forza, in questa fase della vita. Questa aiuta le ragazze, sostenute dall'immaginazione paterna, a liberarsi ed incontrare le richieste di adattamento al mondo paterno, mentre definiscono il proprio Io nel genere femminile aprendosi all'altro sesso, attraverso la dinamica dell'opposizione dei sessi. Basandosi sulla teoria classica e post‐junghiana, l'Autrice presenta materiale empirico raccolto durante un lavoro antropologico in una scuola primaria di Copenhagen che include sogni, disegni e racconti che mostrano come l'eroina femminile emerga e diventi un elemento importante nel risolvere le crisi individuative che le ragazze possono incontrare entrando nel sistema educativo, e poi avventurandosi nel mondo. Viene presentato un caso clinico che collega i concetti a partire dall'età prescolare fino ad una crisi di mezza età. В статье предлагается новый взгляд на индивидуацию в детском возрасте. Так, ночные кошмары дошкольников рассматриваются как проявление первого индивидуационного кризиса и этап выхода ребенка из симбиоза с материнским контейнером/матерью. Автор пишет о девочках и предполагает, что хотя архетип Героини и не получил должного внимания, он играет жизненно важную роль в их индивидуации. Героиня – это женский аналог архетипа Героя, который в патриархальной культуре является общепризнанным источником развития на данном этапе. Сталкиваясь с игрой противоположностей, девочки, при поддержке отца и использовании воображения, обращаются к архетипу Героини, чтобы сепарироваться от матери и адаптироваться к отцовскому миру через выбор фемининной эго‐идентичности и сохранение открытости по отношению к другому полу. Основываясь на классической и пост‐юнгианской теории, автор приводит эмпирический материал сновидений, рисунков и историй, собранный в ходе полевых антропологических исследований в одной из начальных школ Копенгагена, иллюстрируя проявление архетипа Героини и его роль как важного элемента в разрешении кризиса развития и индивидуации, с которым девочки могут встретиться при попадании в систему образования и далее на своем жизненном пути. Клиентский случай иллюстрирует связь между нерешенными задачами в дошкольном возрасте и кризисом среднего возраста. Este artículo ofrece una nueva perspectiva sobre la individuación temprana, por ejemplo, considerando las pesadillas de los preescolares como expresión de una primera crisis de individuación y parte de la separación del niño de la simbiosis con la madre/madre contenedora. Centrándose en las niñas, la autora sugiere que la heroína desempeña un papel subestimado pero vital en la individuación de las niñas. La heroína es la contrapartida femenina del héroe masculino, que en una cultura patriarcal se ha asumido comúnmente como la fuente de apoyo en esta etapa. Permite a las niñas – sostenidas por el padre y la imaginación – liberarse a sí mismas y satisfacer las exigencias de adaptación al mundo paterno, junto a una perspectiva de género femenina en el desarrollo de su ego y una apertura al otro sexo donde los opuestos están en juego. Basándose en la teoría clásica y post‐Junguiana, la autora presenta material empírico recopilado durante un trabajo de campo antropológico en una escuela primaria de Copenhague e incluye sueños, dibujos y narraciones para mostrar cómo surge la heroína y se convierte en un elemento importante para resolver la crisis de desarrollo e individuación que pueden encontrar las niñas al entrar en el sistema educativo y aventurarse más en el mundo. El caso de una paciente vincula la falta de resolución en su etapa preescolar con una posterior crisis en la mediana edad. 学前儿童的自性化危机及自我的性别化——在女孩发展中强调女性英雄 本文从一个新的角度探讨了早期自性化的问题, 例如, 将学龄前儿童的噩梦视为第一次自性化危机的一种表现, 也被视为儿童与包含母亲/母性的共生关系分离的一部分。以女孩为重点, 作者认为女英雄在女孩的个性化过程中扮演着重要的, 却未被充分揭示的角色。女英雄是男英雄的女性对应物, 在父权文化中, 男英雄通常被认为可以为这一阶段的发展提供支持。她使女孩——在父亲和想象力的支持下——解放自我, 满足适应父权世界的要求, 同时将自我性别化为女性, 这一女性对处于对立面的另一性别持开放态度。作者以古典和后荣格理论为基础, 介绍了在哥本哈根一所小学进行人类学实地调查时收集到的经验材料, 并通过梦境、绘画和叙事来展示女性英雄是如何出现, 以及她如何作为重要的因素, 解决女孩在进入教育系统和进一步走向世界时可能遇到的发展性和自性化的危机。文章介绍了一个个案, 其中学前教育中的未决问题与后来的中年危机联系起来。